Midrash in context exegesis in formative Judaism - Neusner, Jacob, 1932- (Philadelphia, PA Fortress, 1983)
Includes bibliographical references and indexes.
Keywords: Midrash -- history and criticism; Bible. O.T. -- criticism, interpretation, etc. -- Jewish; Rabbinical literature -- history and criticism